2009
DOI: 10.1111/j.1439-0272.1998.tb01391.x
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in the presence of CD4-like molecules on human spermatozoa

Abstract: The object of the present study was to study if there are differences in the presence of CD4-like molecules on human ejaculated spermatozoa in fertile donors and infertile patients (with globozoospermia). Indirect and absorption enzyme-linked immunosorbent assay and indirect immunofluorescence were applied. The enzymelinked immunosorbent assay data showed that monoclonal anti-human CD4-antibody recognizes an epitope common to the human spermatozoa with normal morphology and round-headed spermatozoa. Localizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…CD4 (cluster of differentiation 4) is a transmembrane glycoprotein found in several mammal cells including spermatozoa (Gobert et al ., 1990; Dimitrova-Dikanarova et al ., 1998). Lavitrano et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CD4 (cluster of differentiation 4) is a transmembrane glycoprotein found in several mammal cells including spermatozoa (Gobert et al ., 1990; Dimitrova-Dikanarova et al ., 1998). Lavitrano et al .…”
Section: Introductionmentioning
confidence: 99%
“…CD4 (cluster of differentiation 4) is a transmembrane glycoprotein found in several mammal cells including spermatozoa (Gobert et al, 1990;Dimitrova-Dikanarova et al, 1998). Lavitrano et al (1997) demonstrated that membrane CD4-like molecules are responsible for the interaction and binding of exogenous DNA in mice sperm.…”
Section: Introductionmentioning
confidence: 99%
“…Several macromolecules on the sperm surface have been implicated as HIV‐1 binding ligands. These include proteins such as the mannose receptor and CD4 and CD4 like proteins . However, several lines of evidence argue against the presence of CD4 on the sperm surface .…”
Section: Introductionmentioning
confidence: 99%